Дослідження складу забруднень робочої рідини гідросистем дорожньо-будівельних машин, тракторів та автомобілів - Русских, В. В.; Russkikh, Viktor (КНТУ, 2013)
В статті розглянуті переваги і недоліки об’ємного гідроприводу перед електричним приводом та механічними передачами, а також переваги та недоліки шестеренних насосів. Визначено, що основним видом зношення деталей шестеренного насосу є абразивне зношення. Наведено, що основна причина виходу з ладу шестеренних насосів є забруднення робочої рідини. Визначено фактичний вміст механічних домішок в робочій рідині гідросистем машин та якісна оцінка забруднень. Purpose of the article determination of actual composition of mechanical admixtures in the working liquid of gidrosistem road – build machines, tractors and cars. Advantages and lacks of by volume gidroprivoda, and also advantages and lacks of cog-wheel pumps, are considered in the article. It is set that the basic type of wear of details of cog-wheel pumps is an abrasive wear, and by principal reason of output them from a line-up is contamination of working liquid. It is set that the basic type of wear of details of cog-wheel pumps is an abrasive wear, and by principal reason of output them from a line-up is contamination of working liquid. The analysis of contaminations and signs of their education and penetration in gidrosistemy of machines is executed. Actual maintenance of mechanical admixtures is certain in the working liquid of gidrosistem. The high-quality estimation of contaminations is executed. The results of researches allow to set the ways of decline of wear of details of cog-wheel pumps, due to the decline of level of contamination of working liquid.
Researches of composition of contaminations of working liquid of gidrosistem road – build machines, tractors and cars
Keywords: гідропривід; шестеренний насос; зношування; робоча рідина; забруднення; gidroprivod; cog-wheel pump; wear; working liquid; contaminations; abrasive particles; class of cleanness